Characterization of plant growth-promoting rhizobacteria isolated from green mustard (brassica juncea) - Anis Munirah Yunus (2017)
Present investigation on "Characterization of Plant Growth-Promoting Rhizbacteria isolated from Green Mustard (Brassica juncea) "was carried out with the three objectives. Firstly, to isolate rhizobacteria Brassica juncea and followed by to characterize rhizobacteria for biological nitrogen fixation, phosphate solubilisation, potassium solubilizing, indole acetic acid production, and plant growth-promoting potential, and select the most promising isolates.
Project paper (B.S.Bi.) - Universiti Putra Malaysia, 2017
English.
Keywords: Rhizobiaceae; Plant growth-promoting rhizobacteria